Rumor detection in Bangla using machine learning & deep learning - Ahmed, Md Istiaq; Anoy, Shoumik Malakar; Nusrat, Elham; Ahmed, Risat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.